Additional records of hoverflies (Diptera: Syrphidae) from Samos island, Greece. - Steenis, Jeroen van; Ent, Leendert-Jan van der; Ssymank, Axel; Zuijen, Menno van; Steenis, Wouter van (ENTOMOLOGIA HELLENICA, 2021)
In connection with the 10th International Symposium on Syrphidae in Lesbos, a pre- and post Symposium collecting expedition was held on the island of Samos, Greece in September 2019. In total 62 species were collected of which 19 are new species to the island of Samos. Moreover Ischiodon aegyptius and Paragus compeditus are new to Greece. The genera Eumerus and Merodon are well investigated in the SE Mediterranean area, and especially the Greek islands. The discovery of respectively five and two new species for Samos during this very short visit shows that with more effort many new species for the fauna of this island are to be expected.